Method for manufacturing visible infrared separation film

A novel method using silver compounds and polymer dispersants in alcohol solvents with ultrasonic irradiation forms a visible-infrared separation membrane, addressing the limitations of traditional sputtering techniques by enabling efficient, cost-effective, and flexible production of membranes that separate visible and infrared light.

JP2025008217AActive Publication Date: 2025-01-20MINEBEA ACCESSSOLUTIONS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023110185
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-20
Estimated Expiration
2043-07-04

AI Technical Summary

Technical Problem

Conventional methods for manufacturing visible-infrared separation membranes, such as dielectric multilayer films, require precise thin film techniques like sputtering, which are time-consuming, costly, and limit the area and shape flexibility, making them difficult to produce effectively.

Method used

A method involving the dispersion of silver compounds and a polymer dispersant in an alcohol solvent, followed by ultrasonic irradiation to form a coating solution, which is then applied and dried to create a visible-infrared separation membrane using metal nanoparticles with controlled spacing and aggregation, allowing for easy production without sputtering.

Benefits of technology

This method enables the easy manufacturing of a visible-infrared separation membrane that can reflect visible light and transmit infrared light, offering flexibility in size and shape, while reducing production time and cost compared to traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008217000002
    Figure 2025008217000002
  • Figure 2025008217000003
    Figure 2025008217000003
  • Figure 2025008217000004
    Figure 2025008217000004
Patent Text Reader

Abstract

To provide a method for manufacturing a visible infrared separation film which can easily manufacture a visible infrared separation film without using a thin film manufacturing technique such as a sputtering technique.SOLUTION: The method for manufacturing a visible infrared separation film includes: a preparation step of dispersing at least one type of silver compound selected from silver oxide and silver carbonate and a polymer dispersant in an alcohol solvent, radiating an ultrasonic wave to the alcohol solvent to disperse the silver compound, and leaving the alcohol solvent in a dark place, thereby preparing an application liquid; and an application film formation step of applying the application liquid obtained by the preparation step on the surface of the base material and drying the surface of the base material.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a visible / infrared separation membrane that reflects visible light and transmits infrared light. [Background technology]

[0002] Conventionally, when separating visible light and infrared light, dielectric multilayer films that reflect the visible light of the incident light while transmitting the infrared light are sometimes used. Dielectric multilayer films are formed by alternately stacking two types of dielectrics with different refractive indices. Such dielectric multilayer films achieve visible / infrared separation by specifically reflecting only the visible light and transmitting the rest due to the dielectric properties by expressing the ideal multilayer thin film interference phenomenon seen in nature in the skin of hairtail fish (hairtail fish).

[0003] A commonly known example is a cold mirror as described in Patent Document 1, which is made by precisely laminating 20 or more thin layers on a substrate by sputtering or the like. Cold mirrors are used as optical filters, particularly in projectors and the like, to remove infrared rays from light sources. As shown in Patent Document 2, cold mirrors are also used as reflectors in head-up displays (HUDs) to cut infrared rays from sunlight entering from the outside and prevent heating. Furthermore, cold mirrors separate sunlight into visible light and infrared light, and are used as the core of a system that uses visible light to generate electricity and infrared light as a heat source, thereby enabling sunlight to be used with high efficiency.

[0004] Recently, a film with a metallic appearance has also become known, which is made of a multilayer film in which about 1000 layers of resins with slightly different refractive indices are alternately stacked. Taking advantage of their appearance and radio wave permeability, such films are used in automobile emblems that are permeable to millimeter wave radar, and as decorative materials for covering the infrared receiving parts of remote controls for home appliances, taking advantage of their infrared permeability. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2006-259124 A [Patent Document 2] Patent No. 6577342 Summary of the Invention [Problem to be solved by the invention]

[0006] Conventional cold mirrors, whose appearance is expressed by structural color, are created by determining the thickness of each layer in nanometer units through optical calculation simulations so that they can specifically reflect only visible light with a smaller number of layers, and then precisely reproducing the determined thickness by sputtering or other methods. However, since a total of more than 20 thin layers are precisely sputtered while changing their components, and the film is ultimately formed to a thickness of 1 micrometer, this requires a long manufacturing time and is very costly. In addition, restrictions on film formation equipment make it difficult to produce a large area, and there is also a problem that there is little freedom in the shape of the substrate.

[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a method for producing a visible / infrared separation membrane that enables easy production without using thin film production techniques such as sputtering. [Means for solving the problem]

[0008] In order to solve the above problems, the present invention employs the following configuration. The method for producing a visible / infrared separation membrane of the present invention includes a preparation step of dispersing at least one silver compound selected from silver oxide and silver carbonate and a polymer dispersant in an alcohol solvent, irradiating the mixture with ultrasonic waves to disperse the silver compound, and then leaving the mixture in a dark place to prepare a coating solution; The method is characterized by comprising a coating film forming step of coating the coating liquid obtained in the preparation step on the surface of a substrate and drying the coating film. Effect of the Invention

[0009] According to the present invention, it is possible to provide a method for producing a visible / infrared separation film that enables easy production without using thin film production techniques such as sputtering. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is a schematic cross-sectional view illustrating a configuration of a visible / infrared separating member including a visible / infrared separating film according to an embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view of a main part of a visible and infrared separating member according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic diagram illustrating an example of the structure of a visible / infrared separation membrane according to an embodiment of the present invention. [Figure 4] FIG. 4 is a schematic diagram illustrating another example of the structure of the visible and infrared separation film according to the embodiment of the present invention. [Diagram 5] 3 is a cross-sectional SEM photograph showing the visible / infrared separation membrane of Example 1. [Figure 6] FIG. 4 is a spectral diagram showing the relationship between the reflectance and transmittance of Example 1 and the wavelength of incident light. [Figure 7] 3 is a cross-sectional SEM photograph showing the visible / infrared separation membrane of Comparative Example 1. [Figure 8] FIG. 4 is a spectral diagram showing the relationship between the reflectance and transmittance of Comparative Example 1 and the wavelength of incident light. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] From the viewpoint of condensed matter physics, a material that reflects visible light while transmitting infrared light does not exist. In other words, in order to obtain the reflection of visible light like a metal, the existence of free electrons is a prerequisite according to the Drude-Sommerfeld model, and at the same time, since the electrons can move freely, it is not possible to have reflection only in a specific wavelength band.

[0012] Therefore, all of the prior art technologies have achieved visible-infrared separation by providing a specific reflection of visible light through the realization of structural color using a dielectric multilayer film. However, there are challenges to structural color using this dielectric multilayer film. First, it is difficult to manufacture because it is a multilayer film with a highly optically designed structure and precisely controlled film thickness on the nanometer order. Second, because it is such a multilayer film, there are limitations such as the need to process it into a large area and the influence of the angle of incidence.

[0013] Therefore, the present inventors have conducted extensive research into the above-mentioned problems. The reason why visible light reflection and infrared light transmission are not compatible is that there are no constraints on the movement of free electrons. Therefore, if free electrons can be physically confined in a nano-sized region, they will be able to follow short-wavelength light (electromagnetic waves) and behave as free electrons, but for long-wavelength light (electromagnetic waves), they will not be able to behave as free electrons due to physical confinement, so it is expected that electromagnetic waves will be transmitted, and this is thought to be possible.

[0014] The condition for realizing these is that the structure contains metal nanoparticles that are independent of each other. However, simply containing independent metal nanoparticles is not enough. In other words, metal nanoparticles have localized surface plasmon resonance (hereinafter referred to as LSPR), and the absorption and reflection caused by the resonance of free electrons due to this are mixed together, so the desired effect cannot be obtained.

[0015] Therefore, we found that even for nanoparticles with LSPR, it is possible to achieve both visible light reflection and infrared light transmission by utilizing the newly discovered phenomenon described below, in which electrons pass between nanoparticles and behave relatively freely.

[0016] Traditionally, basic and applied research on metal nanoparticles has been premised on interest in LSPR, which can be used to confine light in a nanoscale and trigger enhancement or energy conversion. For this reason, research has not assumed the transfer and movement of electrons due to tunneling between nanoparticles, and simulations using the finite difference time domain method (FDTD method) that considers only the behavior inside independent nanoparticles have been the basis. Although it is known that electrons leak out (hereinafter referred to as spillout), even if only slightly, samples in which the interparticle distance is sufficiently large using a dispersant (ligand) have been the subject of research so that this can be ignored to avoid discrepancies with simulations.

[0017] Meanwhile, detailed investigations of the behavior of a laminated film of silver nanoparticles, a type of metal nanoparticle, in which the interparticle distance is sufficiently close (approximately 2 nm or less) due to the selection of a dispersant revealed a phenomenon that could not be explained by LSPR, but could only be explained by assuming that electrons pass between the nanoparticles and "behave as if they were free electrons." In other words, they found electrons that do not simply spill out, but behave as if they formed a new band between the particles.

[0018] Based on this discovery, the researchers found that by creating a state in a film that allows electrons to tunnel between multiple metal nanoparticles, they can achieve the same effect as amorphous nanoparticles.

[0019] To simultaneously reflect visible light and transmit infrared light, it is necessary for metal nanoparticles with a long diameter of 25 nm or less to exist independently in the film. Conventionally, tunneling between particles has not been taken into consideration in functional films containing metal nanoparticles, but a phenomenon has been discovered that cannot be realized without tunneling. When metal nanoparticles are sufficiently close to each other, tunneling occurs and electrons move freely across multiple nanoparticles, allowing them to behave like a pseudo "shapeless and sufficiently small metal nanostructure."

[0020] The problem here is when the metal nanostructure is larger than a certain size. When the metal nanostructure is larger than a certain size, it responds like a metal even to long-wavelength light (electromagnetic waves), significantly impeding the transmission of light (electromagnetic waves) in the infrared range. To prevent this, a measure was devised to separate compact aggregates of metal nanoparticles while maintaining a minimum distance, taking advantage of the fact that tunneling between metal nanoparticles decreases exponentially with distance. In the past, the requirement of sufficiently separating these aggregates was not met, so reflection and absorption extended into the infrared range, making it impossible to obtain an effective visible-infrared separation membrane.

[0021] Hereinafter, a method for producing a visible / infrared separation membrane according to an embodiment of the present invention will be described.

[0022] In this embodiment, visible light refers to light having a wavelength in the range of 380 to 750 nm. Infrared light refers to light having a wavelength in the range of 850 to 1600 nm. Light having a wavelength of 1600 nm or more is excluded because it is significantly influenced by the absorption of the transparent resin substrate.

[0023] The visible / infrared separation membrane produced by the manufacturing method of this embodiment includes aggregates of metal nanoparticles having a long axis of 25 nm or less, the surface-to-surface distance between the metal nanoparticles inside the aggregates is 2 nm or less, the size of the aggregates is 50 nm or less, the aggregates are spaced apart from each other by a distance of 5 nm or more, and the visible / infrared separation membrane has a thickness of 120 nm or less. Prior to describing the manufacturing method of this embodiment, a visible / infrared separation membrane will be described below.

[0024] The visible infrared separation film may be laminated on a primary layer formed on a substrate. The visible infrared separation film is a thin film with a thickness of 120 nm or less, and is therefore easily affected by the unevenness of the substrate. Therefore, a primary layer may be provided to smooth the substrate surface. In addition, a clear layer may be laminated on the visible infrared separation film. The visible infrared separation film contains silver nanoparticles and is easily damaged, so a clear layer may be provided to protect it.

[0025] That is, as shown in Fig. 1, a visible / infrared separating member 5 may be provided with a substrate 1, a primary layer 2 formed on the substrate 1, a visible / infrared separating film 3 formed on the primary layer 2, and a clear layer 4 formed on the visible / infrared separating film 3. The primer layer 2 is formed, for example, by applying an acrylic urethane primer paint. The clear layer 4 is formed, for example, by applying an acrylic urethane clear paint.

[0026] The substrate 1 may be disposed on the light incident surface side of the visible / infrared separation film 3, or may be disposed on the light exit surface side of the visible / infrared separation film 3. When the substrate 1 is disposed on the light incident surface side, it is preferable that the substrate 1 has a transmittance of 90% or more for visible light and infrared light. This is to prevent the visible light and infrared light contained in the incident light from being absorbed by the substrate 1 before passing through the visible / infrared separation film 3. Examples of such a substrate 1 include polymethyl methacrylate, polycarbonate, and acrylic urethane. On the other hand, when the substrate 1 is disposed on the light exit surface side, it is preferable that the substrate 1 has a transmittance of 90% or more for infrared light. This is to prevent the infrared light contained in the exit light of the visible / infrared separation film 3 from being absorbed by the substrate. Examples of such a substrate 1 include polymethyl methacrylate, polycarbonate, and acrylic urethane.

[0027] As shown in FIG. 2 and FIG. 3, the visible infrared separation film 3 includes an aggregate 3B formed by aggregating metal nanoparticles 3A having a major axis of 25 nm or less. The aggregate 3B is formed by aggregating at least two or more metal nanoparticles 3A. Inside the aggregate 3B, two or more metal nanoparticles 3A are close to each other with a surface-to-surface distance of 2 nm or less. The aggregates 3B are spaced apart from each other with a surface-to-surface distance of 5 nm or more. In this way, it is possible to identify the aggregate 3B by measuring the surface-to-surface distance. The surface-to-surface distance of the metal nanoparticles 3A is the shortest distance between the particle surfaces of the metal nanoparticles 3A. The surface-to-surface distance of the aggregate 3B is the shortest distance between the surfaces of the aggregate 3B.

[0028] Moreover, the visible / infrared separation film 3 contains a resin made of a polymer dispersant in addition to the metal nanoparticles 3A.

[0029] The content of the metal nanoparticles 3A contained in the visible / infrared separation film 3 is preferably 35 to 50% in terms of volume filling rate (%). The remainder may be a resin (polymer dispersant). When the content of the metal nanoparticles 3A is in the range of 35 to 50%, visible light of incident light can be reflected and infrared light can be transmitted. If the content of the metal nanoparticles 3A is 50% or more, there is a risk that the surface distance of the aggregates cannot be made 5 nm or more. If the content of the metal nanoparticles 3A is less than 35%, the proportion of particles is too small and the metallic appearance cannot be maintained.

[0030] When the metal nanoparticles 3A are Ag (silver), the shape of the metal nanoparticles is preferably any one of a sphere, a disk, a rod, or a rectangle. In addition, it is preferable that the shape of each metal nanoparticle is uniform. FIG. 3 shows a case where the metal nanoparticles 3A are spherical and the shape of each metal nanoparticle 3A is uniform. However, when the metal nanoparticles are In (indium), the shape of the metal nanoparticles is preferably a shape that does not correspond to any of a sphere, a disk, a rod, or a rectangle, that is, an irregular shape as shown in FIG. 4. As expected from silver halide photography, irregular silver nanoparticles have a blackish appearance and hinder reflection. Therefore, this can be avoided by using nanoparticles with a uniform shape. On the other hand, indium nanoparticles can be obtained by vapor deposition or sputtering, and although they have an irregular shape, they have a silvery white appearance, so there is no problem.

[0031] The major axis of the metal nanoparticles 3A is preferably 25 nm or less. By having a major axis of 25 nm or less, infrared light can be transmitted. The major axis of the metal nanoparticles 3A is the maximum diameter of the metal nanoparticles 3A when observed with a SEM or TEM.

[0032] As described above, the visible / infrared separation film 3 contains a resin as well as metal nanoparticles 3A. The resin is present between the metal nanoparticles 3A and between the aggregates 3B, and separates the metal nanoparticles 3A from one another, and contributes to maintaining the independence of the metal nanoparticles 3A even after they are aggregated, thereby maintaining them as aggregates 3B. Therefore, although the metal nanoparticles 3A are aggregates, they do not come into contact with one another, and the free movement of electrons is restricted.

[0033] The surface distance between the metal nanoparticles 3A inside the aggregate 3B must be 2 nm or less. This allows free electrons to pass between the nanoparticles and behave somewhat freely, allowing visible light of the incident light to be reflected. In addition, infrared light can be transmitted. The surface distance between the metal nanoparticles 3A may be more than 0 nm.

[0034] In addition, the surface distance between the aggregates 3B is preferably 5 nm or more. If the surface distance between the aggregates 3B of metal nanoparticles is less than 5 nm, infrared light will be reflected, which is not preferable. The surface distance between the aggregates 3B may be, for example, 20 nm or less or 10 nm or less.

[0035] Furthermore, among the aggregates contained in the visible / infrared separation membrane, it is preferable that 70% or more, by number, of aggregates have an aspect ratio (major axis / minor axis), which is the ratio of the major axis to the minor axis, in the range of 1 to 2. It is preferably 90% or more. This eliminates as many long nanoparticles or agglomerates that can respond to infrared light as possible, thereby suppressing reflection and absorption in the infrared region.

[0036] The thickness of the visible / infrared separation film is 120 nm or less. The thickness of the visible / infrared separation film may be 100 nm or less. Also, it may be 50 nm or more, or 30 nm or more. By making the thickness of the visible / infrared separation film 120 nm or less, it is possible to reflect visible light out of the incident light and transmit infrared light.

[0037] The metal nanoparticles are preferably made of either silver (Ag) or indium (In), and are particularly preferably made of silver (Ag).

[0038] The long diameter of metal nanoparticles is measured by cutting out a cross section with a microtome or similar and measuring with a SEM. The magnification is set to 100,000 to 150,000 times, and 10 nanoparticles are randomly selected within the observation field and measured. Measurements are performed in five different fields of view, and the average value is taken as the long diameter.

[0039] The method for measuring the surface distance between metal nanoparticles is to cut out a cross section using a microtome or similar and measure using a SEM. The magnification is set to 100,000 to 150,000 times, and 10 locations between particles are randomly selected from the mass of nanoparticles within the observation field and measurements are taken. Measurements are taken in five different locations and the average value is taken as the surface distance.

[0040] The aspect ratio of metal nanoparticles is measured by cutting out a cross section using a microtome or the like and measuring it with a SEM.

[0041] The method for measuring the percentage of metal nanoparticles with an aspect ratio (major axis / minor axis) in the range of 1 to 2 is to cut out a cross section using a microtome or similar, observe it with a SEM, and calculate the aspect ratio of all nanoparticles present within the field of view. This is done in five different fields of view, and the percentage is calculated from the average.

[0042] The polymer dispersant preferably has a styrene-maleic anhydride resin structure, in which a portion of the maleic anhydride is modified with a polyalkylene glycol having a terminal hydroxyl group or a polyalkylene glycol having a terminal amino group. The polyalkylene glycol preferably has a molar ratio of polyethylene glycol chains to polypropylene glycol chains of 6 / 4 to 8 / 1 and a molecular weight of 500 to 3000. By using a polymer dispersant having such a configuration, it is possible to keep the metal nanoparticles stably dispersed inside the visible / infrared separation membrane.

[0043] Moreover, the polymer dispersant preferably has an acid value of 150 or less, which can suppress oxidation of the silver nanoparticles.

[0044] Next, a method for producing the visible / infrared separation film of the present embodiment will be described. The method for producing the visible / infrared separation film of the present embodiment can be produced by forming a single laminated film on a substrate, instead of laminating multiple thin films having different refractive indices alternately as in the conventional method.

[0045] That is, the method for producing a visible / infrared separation membrane of the present embodiment includes a preparation step of preparing a coating liquid, and a coating film formation step of spraying the coating liquid onto the surface of a substrate and then drying the coating liquid. Each step will be described below.

[0046] In the preparation process, at least one silver compound selected from silver oxide and silver carbonate and a polymer dispersant are dispersed in an alcohol solvent, then the silver compound is reduced and dispersed by irradiating ultrasonic waves, and then the coating solution is prepared by leaving it in a dark place for 3 to 6 months. If the coating solution immediately after reduction and dispersion is applied, aggregates cannot be formed in the coating film. By leaving the preparation solution in a dark place for 3 to 6 months, the silver nanoparticles naturally aggregate with each other, and aggregates of 50 nm or less are generated. Leaving it in a dark place means leaving it in a state where no light is incident on the coating solution.

[0047] The polymer dispersant may be one mentioned above. Polymer dispersants having a styrene-maleic acid copolymer structure and polymer dispersants in which a part of the maleic anhydride is modified with a polyalkylene glycol having a terminal hydroxyl group or a polyalkylene glycol having a terminal amino group are already commercially available. For example, styrene-maleic acid copolymers as base resins include SMA (registered trademark) Base Resin 1000, 2000, 3000, SMA Ester Resin 1440, 2625 (all manufactured by Cray Valley USA, LLC), Alastar 700 (manufactured by Arakawa Chemical Industry Co., Ltd.), etc. The acid value of these base resins having an SMA structure is as high as 175 to 500. Disperbyk 190 and 2015 (non-volatile content 40%, acid value 10, manufactured by BYK) have a styrene-maleic anhydride resin structure, in which a portion of the maleic anhydride is modified with a polyalkylene glycol having a terminal hydroxyl group, etc., and the acid value of the non-volatile content is both 25.

[0048] Thus, while commercially available polymer dispersants include those with high and low acid values, the acid value is fixed at a specified value. Therefore, by using SMA Base Resin 1000, which is one of the polymer dispersants having a styrene-maleic acid copolymer structure, and modifying part of the maleic anhydride in the styrene-maleic acid copolymer structure with a polyalkylene glycol having a terminal hydroxyl group or a polyalkylene glycol having a terminal amino group, the acid value can be adjusted to 150 or less.

[0049] The alcohol solvent is at least one selected from the group consisting of methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-methyl-1-propanol, and 1-methoxy-2-propanol.

[0050] The at least one silver compound selected from silver oxide and silver carbonate is not particularly limited as long as it is in powder form.

[0051] The amount of the polymer dispersant added to the silver compound is 2 to 25% by mass in terms of the mass ratio of the non-volatile matter, and the concentration of the silver compound in the alcohol solution is 5 to 40% by mass.

[0052] When silver oxide or silver carbonate is added to an alcoholic solvent in which a polymeric dispersant has been dissolved, a heterogeneous solid-liquid two-phase alcoholic solution is obtained in which the silver oxide or silver carbonate is dispersed. When ultrasound is applied to this alcoholic solution, air bubbles (cavitation) are generated in the solution. As the cavitation is generated and collapsed, a high-temperature local reaction field is generated in the solution, helping to generate radicals, which in turn advances the sonochemical reaction. In other words, even without the addition of a separate reducing agent, a decomposition and reduction reaction occurs in the silver oxide or silver carbonate, generating metallic silver, which precipitates in the form of silver nanoparticles. The reaction formula is shown below.

[0053] Ag2O → 2Ag + O2↑ Ag2CO3→ 2Ag + 1 / 2O2↑+ CO2↑

[0054] As shown in the above reaction formula, oxygen (in the case of silver oxide) or oxygen and carbon dioxide (in the case of silver carbonate) are generated as by-products, but these are volatile, and the alcohol solvent is also volatile, and both of these substances are non-corrosive components. Therefore, by performing the coating film formation process, it is possible to easily manufacture a visible-infrared separation membrane consisting of silver nanoparticles and a polymer dispersant.

[0055] The alcohol solution after dispersing the silver compound by irradiating ultrasonic waves is further left in a dark place. This allows the aggregation of silver nanoparticles to proceed, and the metal nanoparticles in the visible / infrared separation membrane can aggregate with a surface distance of 2 nm or less to form aggregates with a size of 50 nm or less. There is no limit to the leaving time as long as aggregates of 50 nm or less can be formed, but it is preferable to leave it for, for example, 3 months or more. There is no particular limit to the upper limit of the leaving time, but it may be, for example, 6 months or less. The starting point of the leaving time is the end of the ultrasonic irradiation.

[0056] Next, in the coating film forming step, the coating liquid obtained in the preparation step is applied to the surface of the substrate by, for example, spraying, and then drying. The drying may be performed, for example, in an atmosphere of 5 to 80°C. A general sprayer may be used as a means for spraying the coating liquid. There are no particular limitations on the spray conditions, but examples include adjusting the needle so that the coating liquid discharge rate is 30 to 60 mL / min and setting the atomization pressure to 0.2 to 0.3 MPa. By spraying the coating liquid, the alcohol evaporates before the coating liquid reaches the surface of the substrate, and the aggregation of the metal nanoparticles progresses further. This forces independent nanoparticles that have not fully aggregated when left to aggregate. As a result, such free nanoparticles are prevented from filling the gaps between the aggregates, and it becomes possible to make the surface distance between the aggregates in the visible / infrared separation membrane 5 nm or more.

[0057] In the coating film formation process, a form in which the coating liquid is applied to the surface of the substrate by spraying has been described; however, this embodiment is not limited to this, and various liquid application methods such as screen printing and spin coating may also be used.

[0058] As described above, the visible / infrared separation film of the present embodiment is formed by a coating method, so that it is possible to increase the area and also to increase the degree of freedom in the shape of the substrate. Moreover, according to the method for producing the visible and infrared separation film of this embodiment, the visible and infrared separation film can be easily produced without using a thin film production technique such as a sputtering method.

[0059] The visible / infrared separation membrane of this embodiment can achieve a visible light reflectance of 40% or more and an infrared light transmittance of 60% or more. Here, the visible light reflectance is the average value of the reflectance of light having a wavelength in the range of 380 to 750 nm. The infrared light transmittance is the average value of the transmittance of light having a wavelength in the range of 850 to 1600 nm.

[0060] In addition, since the visible / infrared separation film of this embodiment is formed by the coating method as described above, it can be made large in area and the degree of freedom in the shape of the substrate can be increased. Furthermore, the visible / infrared separation film of this embodiment can be easily manufactured without using thin film manufacturing techniques such as sputtering. In addition, it is not necessary to precisely stack tens of layers of films alternately as in the conventional dielectric multilayer film, and it can be easily manufactured in a short time. EXAMPLES

[0061] Examples of the present invention will now be described.

[0062] Example 1 As a polymer dispersant, 4 g of Disperbyk 2015 (non-volatile content 40%, acid value 10, manufactured by BYK) was dissolved in 100 g of 2-propanol (isopropyl alcohol), and 25 g of silver oxide powder was suspended. The acid value of the non-volatile content of this polymer dispersant was 25, and the content ratio of the polymer dispersant was 6.4% by mass relative to the silver oxide. Disperbyk 2015 has a styrene-maleic anhydride resin structure, and a part of this maleic anhydride was modified with a polyalkylene glycol having a terminal hydroxyl group.

[0063] Next, this suspension was irradiated at 20 KHz for 2 hours at room temperature of 15 to 17°C. Next, it was filtered through a 1 μm filter to obtain a brown silver nanoparticle dispersion. Furthermore, this silver nanoparticle dispersion was left for 6 months at room temperature of 15 to 17°C. During the leaving, the incidence of light on the dispersion was blocked. In this way, a coating liquid was prepared.

[0064] The silver nanoparticle dispersion liquid prepared as described above was diluted with ethyl alcohol at a ratio of 1:3. An acrylic urethane primer paint was applied to a substrate made of polymethyl methacrylate, dried and cured to prepare a test piece. The diluted dispersion liquid was spray-painted onto this test piece and dried at 80°C for 30 minutes. The conditions for spray-painting the silver dispersion liquid were as follows: Anest Iwata LPH-101 was used as an air spray gun, the needle was adjusted so that the discharge rate of the coating liquid was 30 to 60 mL / min, the atomization pressure was set to 0.2 to 0.3 MPa, and the silver nanoparticles were applied only once. After that, an acrylic urethane clear paint was applied to protect the silver nanoparticles. In this way, the visible infrared separation membrane of Example 1 was produced.

[0065] Comparative Example 1 The silver nanoparticle dispersion filtered through a 1 μm filter was not left to stand, and the silver nanoparticle dispersion was diluted with ethyl alcohol at a ratio of 1:2. An acrylic urethane primer paint was applied to a substrate made of polymethyl methacrylate, dried and cured to prepare a test piece. The diluted dispersion was spray-painted on the test piece, and dried at 80° C. for 30 minutes. The conditions for spray-painting the silver dispersion were as follows: Anest Iwata LPH-101 was used as an air spray gun, the needle was adjusted so that the discharge amount of the coating liquid was 60 mL / min, the atomization pressure was set to 0.2 to 0.3 MPa, and two coats were applied. Thereafter, the visible infrared separation membrane of Comparative Example 1 was produced in the same manner as in Example 1 above.

[0066] (Evaluation method) Visible light reflectance and infrared light transmittance were measured using Hitachi High-Tech Science's UH4150 or a spectrophotometer capable of measuring up to the near-infrared region. Test pieces were cut to a size that could be installed in the measurement device and then set into the device. The scan speed was 300 nm / min in the visible region and 750 nm / min in the infrared region, and the visible-infrared viewing switch was set to long wave 850 nm. Measurements were taken at a sampling interval of 1 nm, with automatic detector switching and no use of a light-reducing plate, and output as Excel data. The average reflectance and transmittance in the specified wavelength band were then calculated to obtain the measured value.

[0067] In addition, the major axis of the metal nanoparticles, the surface-to-surface distance between metal nanoparticles inside the aggregate, the size of the aggregate, the surface-to-surface distance between aggregates, the film thickness, and the proportion of aggregates with an aspect ratio of 1 to 2 were measured by the methods described above.

[0068] The results are shown in Table 1.

[0069] [Table 1]

[0070] As shown in Table 1, the visible / infrared separation membrane of Example 1 was within the range of the present invention, with a visible light reflectance of 40% or more and an infrared light transmittance of 60% or more, and was able to reflect visible light and transmit infrared light. On the other hand, the visible / infrared separation membrane of Comparative Example 1 had a surface distance between aggregates of less than 3 nm, which did not satisfy the range of the present invention. As a result, the infrared light transmittance was less than 60%, and infrared light could not be sufficiently transmitted. [Explanation of symbols]

[0071] 1...substrate, 2...primary layer, 3...visible / infrared separation film, 3A...metal nanoparticles, 3B...aggregate, 4...clear layer, 5...visible / infrared separation member.

Claims

1. A preparation step of dispersing at least one silver compound selected from silver oxide and silver carbonate and a polymer dispersant in an alcohol solvent, dispersing the silver compound by irradiating with ultrasonic waves, and then leaving the mixture in a dark place to prepare a coating solution; A method for producing a visible / infrared separation membrane, comprising: a coating film forming step of applying the coating liquid obtained in the preparation step to a surface of a substrate and drying the applied coating liquid.

2. The method for producing a visible / infrared separation membrane according to claim 1, wherein the concentration of the silver compound in the alcohol solvent is 5 to 40 mass%.

3. The alcohol solvent is at least one selected from the group consisting of methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-methyl-1-propanol, and 1-methoxy-2-propanol. The method for producing a visible / infrared separation membrane according to claim 1.

4. The method for producing a visible / infrared separation membrane according to claim 1 , wherein the polymer dispersant has an acid value of 150 or less.

5. The polymer dispersant has a styrene-maleic anhydride resin structure, and a part of the maleic anhydride is modified with a polyalkylene glycol having a terminal hydroxyl group or a polyalkylene glycol having a terminal amino group. The method for producing a visible-infrared separation membrane according to claim 4.

6. The method for producing a visible-infrared separation membrane according to claim 1, wherein the amount of the polymer dispersant added to the silver compound is 2 to 25% by mass of non-volatile matter.

Citation Information

Patent Citations

  • Infrared-transmissive black film, and filmed substrate and image forming apparatus using infrared-transmissive black film

    JP2012047948A

  • Method for producing composition liquid for forming silver mirror film layer, and method for forming silver mirror film layer

    JP2017002219A

  • Transmissively read optical recording medium

    US4999278A

  • Cold mirror

    JP2006259124A

  • Cold mirror for head-up display device, and head-up display device

    JP6577342B2